Investigating the Feasibility of using Growth Increments for Age Determination of Norway Lobster (Nephrops Norvegicus) and Brown Crab (Cancer Pagurus). Issue 4 (1st July 2015) - Sheridan, Michael; Officer, Rick; O'Connor, Ian; Lordan, Colm
Abstract: It has recently been confirmed that some species of decapod crustacean retain their gastric mill and calcified region of the eyestalks throughout their moults. It had previously been assumed that crustacea lost all growth structures that could potentially record age information, such as the bones and otoliths in fish, through moulting. In this study, a novel preparation method was used for observing growth increments within these calcified structures of Nephrops norvegicus and Cancer pagurus (Linnaeus, 1758 ). This method involved: boiling, drying, resin embedding, sectioning, and polishing the gastric mill and eyestalks. Clear and readable growth increments were observed in longitudinal sections of the mesocardiac ossicle of the gastric mill for N. norvegicus, and longitudinal sections of the zygocardiac ossicle of the gastric mill for C. pagurus . Growth increments were also observed in longitudinal sections of the calcified region of the eyestalk for N. norvegicus . Validation is needed to confirm the periodicity of these growth increments.